2017
DOI: 10.1155/2017/4396723
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Field-Enhanced Morphology of Tin Oxide Nanomaterials for Gas Sensing Applications

Abstract: We studied the effect of an external magnetic field (up to 0.31 T) on the growth of SnO 2 nanowires fabricated using the horizontal vapor phase growth (HPVG) technique. The morphology of the nanowires was characterized by using scanning electron microscopy (SEM), and the chemical composition was characterized by energy dispersive X-ray (EDX) analysis. We found that the length of nanowires was significantly enhanced by the application of EMF. The aspect ratio, as well as the density of the fabricated nanowires,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The magnetic field also reported that the length of nanowires is significantly changed. Using Hydrogen Sulfide gases to evaluate SnO 2 nanowire for meat spoilage application [22]. The study was done using 3 different curing times (4,6, and 8 h) with 1200 °C growth temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The magnetic field also reported that the length of nanowires is significantly changed. Using Hydrogen Sulfide gases to evaluate SnO 2 nanowire for meat spoilage application [22]. The study was done using 3 different curing times (4,6, and 8 h) with 1200 °C growth temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of essential oils also reduced the concentration of hexathiane and cyclic octaatomic sulfur in stored samples. The significant presence of these components was detected by GC-MS-SPME in spoiled pork by Briones et al (2017), who mentioned that these compounds are associated with the unpleasant odor in the samples of spoiled meat. However, it is difficult to assess the effect of EOs on the sensorially evaluated odor of the examined turkey meat since, for example, it is difficult to evaluate the contribution to the odor of those meat-derived compounds whose decrease in concentration was affected by these essential oils.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct metal oxide nanomaterials were successfully fabricated through the said technique for sensor applications. For instance, iron oxide nanoparticles and zinc oxide nanomaterials and different nanostructures of tin oxide were fabricated successfully via HVPG for glucose detection [10] and gas sensing application [11,12,13], respectively. Moreover, this said technique was also used to produce the distinct nanocomposites for coating application including silver-titanium dioxide [14,15,16,17] and silver-graphene [18].…”
Section: Introductionmentioning
confidence: 99%